Does consumption of pearl millet cause goiter? A systematic review of existing evidence - Anitha, Seetha; Upadhyay, Shweta; Grando, Stefania; Kane-Potaka, Joanna (Frontiers in Nutrition, 2024)
Millets (defined here to also include sorghum) have been consumed in Asian and African countries for centuries, and have in recent years become increasingly popular in Western countries, especially because of their proven health and environmental benefits. Nevertheless, some concerns have been raised that their consumption can interfere with thyroid function and cause goiter. This systematic review aimed to investigate the link between millet consumption and goiter. We found nine papers that were relevant to this topic and included them in this review. Among nine papers eight were on pearl millet and one was on fonio millet. The findings of the review indicate that published literature on the association of pearl millet and increased goiter prevalence are not compelling and strong enough to assert that pearl millet consumed as part of a balanced diet can lead to goiter in the general population. To ensure appropriate factual messaging about millets, we need more scientific research to conclusively state whether millet consumption mediates goitrogenic effects.